The Power of Language Learning Beyond the Classroom to English Mastery of an EFL Learner - Hariyanti, Yuni; Purwandari, Junita Duwi (Journal of Languages and Language Teaching, 2022)
Language learners have come to an era in which studying outside the classroom is well-facilitated by technology development. Along with this advancement, there is a wider chance to learn things outside the classroom, including language. In the Indonesian context, many students have done wider exploration to improve their English exposure through various activities. This study aims to reveal the learning strategies done by a successful EFL learner through case study research. The result shows that online games, e-books, and movies are some of the prominent learning tools ofÂ  Language Learning Beyond the Classroom (LLBC) to enhance language exposure and learnersâ€™ autonomy.